2018
DOI: 10.3390/molecules23020337
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between P-Glycoprotein Expression and Resistance to Endoplasmic Reticulum Stressors

Abstract: Multidrug resistance (MDR) is a phenotype of cancer cells with reduced sensitivity to a wide range of unrelated drugs. P-glycoprotein (P-gp)—a drug efflux pump (ABCB1 member of the ABC transporter gene family)—is frequently observed to be a molecular cause of MDR. The drug-efflux activity of P-gp is considered as the underlying mechanism of drug resistance against P-gp substrates and results in failure of cancer chemotherapy. Several pathological impulses such as shortages of oxygen and glucose supply, alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 199 publications
(241 reference statements)
3
35
0
Order By: Relevance
“…To explain the mechanism by which ATP deprivation leads to this substantial increase in NOX4 levels, we reasoned that this increase is likely to be correlated with induction of ER stress. Previous studies showed that ER stress can be induced by various means, including ATP deprivation [36]. Consistent with this observation, our aforementioned GSEA of TCGA data also revealed a state of energy deprivation as well ER stress induction ( Figure 8E, Figure 6A).…”
Section: Resultssupporting
confidence: 89%
“…To explain the mechanism by which ATP deprivation leads to this substantial increase in NOX4 levels, we reasoned that this increase is likely to be correlated with induction of ER stress. Previous studies showed that ER stress can be induced by various means, including ATP deprivation [36]. Consistent with this observation, our aforementioned GSEA of TCGA data also revealed a state of energy deprivation as well ER stress induction ( Figure 8E, Figure 6A).…”
Section: Resultssupporting
confidence: 89%
“…Previous reports of ABCB1 responses to cellular stress have been contradictory, demonstrating induction or repression, even after exposure to the same stressor (35). These conflicting results might be consistent with the pleiotropic function of ATF4, which is able to orchestrate adaptation and survival or apoptosis depending on cellular context and the severity of the insult.…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, these latter studies suggested that up-regulation of P-gp caused resistance against CP, not by effluxing the anticancer drug out of the tumor cells, but rather via decreasing its apoptotic effect through down-regulating caspase 3. Indeed, P-gp, through its antiapoptotic mechanisms, was reported to promote cellular resistance against compounds that were not P-gp substrates [32]. Alternatively, some studies suggested the other way around, that CP could induce up-regulation of P-gp through caspase 3 [33].…”
Section: Discussionmentioning
confidence: 99%